Efeitos do uso de programas de luz e de triptofano suplementar na dieta sobre o desempenho, comportamento e parâmetros de estresse de leitões recém-desmamados - Gomes, Lívea Maria [UNESP] (2015)
The objective of the present study was to avaluate the effects of light programs (LP) and tryptophan levels (TL) in the diet on performance, blood glucose, plasma profile of cortisol and behavior. A total of 72 piglets weaned at 21 days of age (starting weight 2.33 kg 6,6±) was used. The experimental design was randomized blocks with 24 days duration in a factorial 2 x 2 (LP 12 or 23h light / day and two digestible TL: 2.6 or 5.2 g of L-Trp / kg diet on pre-starter 1 (0-14 days) and 2.4 or 4.8 g of L-Trp / kg diet on prestarter 2 (15-24 days), with 6 repetitions and 3 animals per pen. Glucose blood was determined on d 0 and 24, and cortisol on d 0 and 8. The behavior was observed on d 2, 9, 16 and 23. No effects of PL and NT interaction were observed on performance and blood glucose. In periods of 0- 14 and 0-24 days, the treatments did not influence the daily weight gain, daily feed intake and blood glucose, while feed conversion improved (P <0.05) only in the period of 0-14 days for piglets receiving PL 12h light / day. Treatments did not influence the frequency of “moving” behavior, however there was interaction between PL and NT for plasma cortisol, frequency of “feeding” and “lying” behavior. Piglets that received high NT had lower plasma cortisol level (P <0.05), lower “feeding” behavior (P <0 .05) and increased “lying” behavior (P <0.05) compared to animals that received normal NT when subjected to PL 23 hours light / day. The PL 23h light / day isn’t indicated for piglets, but when this happen, highest tryptophan level in the diet is recommended.